Tick-Borne Viruses and Biological Processes at the Tick-Host-Virus Interface - Kazimírová, Mária; Thangamani, Saravanan; Bartíková, Pavlína; Hermance, Meghan; Holíková, Viera; Štibrániová, Iveta; Nuttall, Patricia A. (Frontiers in Cellular and Infection Microbiology, 2017)
Ticks are efficient vectors of arboviruses, although less than 10% of tick species are known to be virus vectors. Most tick-borne viruses (TBV) are RNA viruses some of which cause serious diseases in humans and animals world-wide. Several TBV impacting human or domesticated animal health have been found to emerge or re-emerge recently. In order to survive in nature, TBV must infect and replicate in both vertebrate and tick cells, representing very different physiological environments. Information on molecular mechanisms that allow TBV to switch between infecting and replicating in tick and vertebrate cells is scarce. In general, ticks succeed in completing their blood meal thanks to a plethora of biologically active molecules in their saliva that counteract and modulate different arms of the host defence responses (haemostasis, inflammation, innate and acquired immunity, and wound healing). The transmission of TBV occurs primarily during tick feeding and is a complex process, known to be promoted by tick saliva constituents. However, the underlying molecular mechanisms of TBV transmission are poorly understood. Immunomodulatory properties of tick saliva helping overcome the first line of defence to injury and early interactions at the tick-host skin interface appear to be essential in successful TBV transmission and infection of susceptible vertebrate hosts. The local host skin site of tick attachment, modulated by tick saliva, is an important focus of virus replication. Immunomodulation of the tick attachment site also promotes co-feeding transmission of viruses from infected to non-infected ticks in the absence of host viraemia (non-viraemic transmission). Future research should be aimed at identification of the key tick salivary molecules promoting virus transmission, and a molecular description of tick-host-virus interactions and of tick-mediated skin immunomodulation. Such insights will enable the rationale design of anti-tick vaccines that protect against disease caused by tick-borne viruses.